Analysis of the effects of thermal cycling on the microtensile shear bond strength of a self-etching and a conventional pit and fissure sealants to dental enamel - Neto, Daniel Sundfeld [UNESP]; Sobrinho, Lourenço Correr [UNESP]; Gonçalves, Luciano S. [UNESP]; Rahal, Vanessa [UNESP]; Machado, Lucas Silveira [UNESP]; De Oliveira, Fernanda Garcia [UNESP]; Valentino, Thiago A. [UNESP]; Sundfeld, Renato Herman [UNESP] (My University, 2013)
Objective: To analyze the effects of thermal cycling on the microtensile shear bond strength of a self-etching and a conventional pit and fissure sealants to dental enamel. Material and Method: Twenty-four healthy human molars extracted for orthodontic reasons, were sectioned in the mesio-distal direction and divided into two groups (n=24) according to the sealant to be applied: GI - conventional sealant Climpro (3M/ESPE) and GII - self-etching sealant Enamel Loc (Premier Dental). The sealants were applied on flattened enamel in matrixes 1 mm in diameter, in accordance with the manufacturers' recommendations. The specimens were stored in distilled water at 37°C for 24 hours. After this, half the samples of both groups were submitted to 500 thermal cycles in 30s baths at temperatures between 5 and 55°C. Forty-eight hours after the samples were made, the microtensile shear test was performed in an Instron 4411 test machine, with a stainless steel wire with a cylindrical cross section of 0.2mm in diameter at a constant speed of 0.5mm/s. The bond strength values were submitted to ANOVA for 2 factors and the fracture patterns were examined under an optical microscope at 65X magnification. Results: Thermal cycling did not influence the bond strength of the two sealants. The conventional sealant Climpro presented a statistically higher microtensile shear bond strength (11.72MPa, 11.34MPa with and without cycling, respectively) than the self-etching sealant Enamel Loc (5.92MPa, 5.02MPa with and without cycling, respectively). Fracture pattern analysis showed the occurrence of 100% of adhesive failures for Enamel Loc, while the conventional sealant Climpro presented 95% of adhesive failures and 5% of mixed failures. Conclusion: The conventional sealant presented higher microtensile shear bond strength to dental enamel in comparison with the self-etching sealant. Thermal cycling did not affect the bond strength of the sealants used in this study.
Keywords: Dental enamel; Microshear; Self-etching and conventionalpit and fissure sealants; Thermal cycling